Synthesis of SO42–/ZrO2 Solid Acid and Na2O/ZrO2 Solid Base Catalysts Using Hydrothermal Method for Biodiesel Production from Low-Grade Crude Palm Oil - Sri Setyaningsih; Maisari Utami; Akhmad Syoufian; Eddy Heraldy; Nasih Widya Yuwono; Karna Wijaya (Universitas Gadjah Mada, 2022)
Biodiesel is a renewable energy source that can be produced through esterification as well as transesterification reactions. This work presents a series of zirconia catalysts synthesized by hydrothermal method on various concentrations in acidic (H2SO4 0.3, 0.5, and 0.7 M) and basic (NaOH 1, 2, 3, and 4 M) solution to get a catalyst with the highest acidity or basicity. Characterizations of the catalysts were performed by FTIR, XRD, SEM-EDX, surface area analysis, acidity, and basicity test. The most active acid catalyst activity was evaluated for the esterification of low-grade crude palm oil (LGCPO), while the solid base catalyst was utilized for the transesterification reaction. The solid acid catalyst of 0.7 M SO42–/ZrO2 60 °C; 24 h was denoted as the most active acid catalyst with a total acidity of 1.86 mmol g–1, while 4 M Na2O/ZrO2 60 °C; 24 h catalyst was considered as the solid base catalyst with the highest total basicity of 3.75 ± 0.12 mmol g–1. The optimized acid catalyst exhibited a 31 times higher acidity than commercial ZrO2. The concentration of free fatty acids (FFA) decreased to 68.87% in the esterification reaction. The solid base catalyst of 4 M Na2O/ZrO2 60 °C; 24 h successfully converted LGCPO into biodiesel by 68.55% through a transesterification reaction.